Characteristics and sexual health service use of MSM engaging in chemsex: results from a large online survey in England. Issue 8 (5th March 2020) - Blomquist, Paula Bianca; Mohammed, Hamish; Mikhail, Amy; Weatherburn, Peter; Reid, David; Wayal, Sonali; Hughes, Gwenda; Mercer, Catherine H
Abstract : Background: Chemsex, the use of select psychoactive drugs to enhance sexual experience, typically among men who have sex with men (MSM), is associated with sexual behaviours with higher STI risk. Understanding patterns of chemsex among MSM as well as the characteristics and sexual health service engagement of chemsex participants is important for developing interventions. Methods: Between 5/2016 to 5/2017, 3933 MSM completed an online survey, recruited in sexual health clinics (SHCs) in England (n=421) and via four social networking/dating apps (n=3512). We described patterns of chemsex in the past year and used multivariable logistic regression to investigate differences in demographics and sexual behaviours by chemsex history. We described history of SHC attendance and STI test in the past year among app-recruited chemsex participants. Results: Chemsex in the past year was reported by 10% of respondents; 19% of SHC-recruited and 9% of app-recruited. Among chemsex participants, 74% had used ≥2 chemsex drugs. In the multivariable model, MSM engaging in chemsex had a raised odds of being HIV-positive (adjusted OR (aOR): 3.6; 95% CI 2.1 to 6.1), aged 30–44 (aOR 1.5 vs <30 years; 95% CI 1.0 to 2.1), being born outside the UK and having engaged in higher risk sexual behaviours in the past 3 months. Chemsex participants also had higher odds of condomless anal sex with partners of different or unknown HIV status, but only among HIV-negative/untested. In the past year, 66% of app-recruited chemsex participants had attended a SHC and 81% had had an STI test. Conclusion: One in 10 MSM recruited through community and clinical settings across England had engaged in chemsex in the past year. Those that did appear to be at greater STI risk but engaged more actively with sexual health services. This highlights the need and opportunity for chemsex-related services in SHCs and robust referral pathways to drug treatment services.